Gross National Happiness and Macroeconomic Indicators in the Kingdom of Bhutan - Balasubramanian, Sriram; Cashin, Paul. (Washington, D.C. : International Monetary Fund, 2019)
This paper examines the origins and use of the concept of Gross National Happiness (or subjective well-being) in the Kingdom of Bhutan, and the relationship between measured well-being and macroeconomic indicators. While there are only a few national surveys of Gross National Happiness in Bhutan, the concept has been used to guide public policymaking for the country's various Five-Year Plans. Consistent with the Easterlin Paradox, available evidence indicates that Bhutan's rapid increase in national income is only weakly associated with increases in measured levels of well-being. It will be important for Bhutan to undertake more frequent Gross National Happiness surveys and evaluations, to better build evidence for comovement of well-being and macroeconomic concepts such as real national income.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet